Exploring the Relationship between Socio-economic Factors and ICT Adoption among Farmers - Chandra, Saurabh; Singh, A K; Ghadei, Kalyan; Pradhan, Sabyasachi (Indian Journal of Extension Education, 2023)
The study was conducted in Uttar Pradesh, India to assess the relationship between ICT tools and socio-economic variables of farmers. The ex-post-facto research design and multi-stage random sample technique were used. The data was collected through personal interviews with farmers. The total sample size of the study was 120 farmers. The study data were analyzed with correlation, multiple regression, and path analysis. The coefficient of determination (R2) revealed that 79.90 per cent of the total variation in the utilization of ICT tools by the farmers was explained by the selected independent variables. The path analysis was used to assess the total effect, which was decomposed into direct, indirect, and residual effects. The variable education (0.358) exerted the highest direct effect, while the total indirect effect of extension contact (0.493) was on the utilization of ICT tools by the farmers. The residual effect was 0.201, which means that 20.10 per cent of the variance could not be explained due to exogenous variables. Overall, the study suggests that education and extension contact are crucial factors that affect the utilization of ICT tools by farmers in Uttar Pradesh for agricultural purposes.
Keywords: ICT; Extension contact; Exogenous variables; Residual effect; Utilization